THE IMPACT OF THE DIGITAL ECONOMY ON THE GROWTH OF SMES AND THE LABOUR MARKET STRUCTURE IN INDONESIA - Tehedi; Ahmad Rizani (BORJUIS: JURNAL OF ECONOMY, 2026)
The digital economy has become a key transformative force in the Indonesian economy, with growth reaching 8.6% and a contribution of 8.4% to GDP in 2024. This study aims to analyse the impact of the digital economy on the growth of SMEs and the labour market structure in Indonesia using a literature review method with a descriptive qualitative approach. The results indicate that the digital economy has a significant positive impact on SME growth, with 70% of SME operators experiencing an increase in revenue of up to 30% after joining the digital ecosystem, and SME growth reaching 83% by 2024. Digitalisation opens up broader market access, improves operational efficiency by reducing marketing costs by up to 42.68%, and provides access to alternative financing through P2P lending fintech platforms, which have channelled Rp37.9 trillion to SMEs. However, the digital transformation of SMEs still faces challenges, including low technology adoption (only 24–26%), low digital literacy (only 18% possess basic digital skills), and limited internet infrastructure (76.8% penetration). In terms of the labour market structure, the digital economy created 4.2 million direct jobs and 15.7 million indirect jobs in 2023, projected to rise to 6.5 million and 22 million by 2025, although 83 million jobs are predicted to be lost due to automation by 2025. The gig economy offers flexibility to 86.6 million workers (59.40% of the total workforce), yet it also creates economic uncertainty, with 28.4% of gig workers labouring 13–14 hours a day without adequate social protection. The digital skills gap remains a major obstacle, with only 1% of the workforce possessing advanced-level skills against a target of 50%. The study recommends strengthening vocational education curricula, implementing mass reskilling and upskilling programmes for 5 million digital talents by 2026–2030, developing equitable digital infrastructure, strengthening regulations to protect gig workers, and providing incentives for SMEs to undergo digital transformation.